The possible association between stage of HIV disease and the nutrient composition of breast milk - De Wet, G. (Bloemfontein : Central University of Technology, Free State, 2013)
Breastfeeding is a major source of childhood nutrition and protection, but with South Africa having one of the highest HIV prevalence in the world the risk of HIV transmission from mother to infant through breastfeeding becomes a major issue. Infant mortality due to malnutrition and infections is also of great concern. Exclusive breastfeeding and giving antiretroviral drugs to the HIV-infected mother and the HIV-exposed infant is one of the most significant ways to improve infant survival rates and reduce transmission of HIV through breastfeeding. Whether HIV disease progression and its metabolic impact on the mother will affect the nutrient composition of breast milk is a question that arises. The aim of this study was to determine the possible association between the stage of HIV disease, as measured by the immunological markers, and the nutrient composition of breast milk. The study population consisted of 60 HIV infected female volunteers who were divided into two groups. Milk and blood samples were obtained from 30 HIV-positive women that was not on any ARV treatment and from 30 HIV-positive women that was on ARV treatment. Their HIV status and treatment regime were obtained from their files. Participants were also asked to complete a questionnaire. Macro-nutrients that were measured included lactose, proteins, fat, total solids and the energy content of the breast milk. This was done on the MIRIS Human milk analyser. The micro-nutrients that were measured were calcium and phosphate on the DXC 800 chemistry analyser. Blood analysis was included to determine the stage of HIV disease progression in the HIV-positive mothers and comprised of a CD4/CD8+ T cell count, viral load and a full blood count. CD4/CD8+ T cells were determined using flowcytometry on the BD FACScalibur. The COBAS AmpliPrep/COBAS TaqMan HIV-1 Test was used for the determination of the viral load and the full blood count was done using a Sysmex XT2000i haematology analyser. When comparing the analysed haematological variables, the white blood cells and red blood cells indicated a significant difference between the two groups. Both of the groups were anaemic. The CD3+ T cell count was higher and the CD4+ T cell count was lower than the reference range in both groups. The median CD4+ T cells and HIV-1 viral load for the HIV with treatment group was higher than the HIV-infected without treatment group. The analyzed milk data yielded no p-value of great significance, suggesting that there was no statistically significant difference recorded of the measured nutrients between mothers receiving treatment and those who did not receive any treatment for HIV. The Spearman Correlation Coefficient was used to determine if HIV disease progression would have an influence on the nutrients that were measured. For the HIV-infected without treatment group, a significant correlation was found between the HIV-1 viral load and percentage total solids in breast milk. For the HIV-infected with treatment group the only positive correlation was between the CD4+ T cell count and the percentage total solids and energy content of the breast milk. No strong positive correlation could be established between the immunological markers of HIV disease progression and the analysed nutrients in the breast milk. Taking this into consideration, HIV-positive mothers can breastfeed their babies even if their HIV status is at a more advance phase, but the emphasis should be placed on exclusive breastfeeding and getting the needed support to breastfeed.
Thesis (M. Tech. (Biomedical technology)) - Central University of technology, Free State, 2013
Keywords: Central University of Technology, Free State - Dissertations; Breast milk; Breastfeeding; Infants - Nutrition; HIV-positive women; AIDS (Disease) in women; Dissertations, academic - South Africa - Bloemfontein